Pengaruh Motivasi, Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. Ori Ginalnest Indonesia - Candra Jonathan Waruwu; Yovie Ernanda; Angelia Sonia Pakpahan; Jeffri Cahyadi; Winda Ardiani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
An export company that builds swallow nests and aims to maintain operational competitiveness, PT. Ori Ginalnest Indonesia, was driven to conduct this study by the importance of optimising staff performance. The study's overarching goal is to dissect the interplay between intrinsic drive, external work discipline, and the physical and social contexts in which employees perform. Quantitative methods based on a causal-associative framework were employed in the research. This study used a saturation sampling strategy to collect data from 80 employees. Multiple linear regression was used to analyse data collected from a questionnaire. Motivation and work discipline were shown to have no significant effect on performance according to the partial test findings. All three independent factors have a substantial impact on employee performance at the same time, as shown by an f-value of 39,812 which is greater than the critical f-value of 2.72 and a significance level of 0.000, which is less than 0.05. According to the results, the two most essential things that can boost productivity in the workplace are making the facility better and making everyone feel more comfortable.